ДУХОВНО-ЕСТЕТИЧНІ КООРДИНАТИ ПОЕТИЧНОГО ДОРОБКУ БОРИСА ГРІНЧЕНКА - Ярослава Вільна; Ігор Хворостяний (International Journal of Innovative Technologies in Social Science, 2019)
The article vents on a comprehensive analysis of general thematic and aesthetic levels of the poetic work of Ukrainian Writer B. Hrinchenko. The conceptual foundations of creation of author’s image in poetic work are revealed. Texts, which are interwoven into a system by «adjacent» motifs, images, intonations are analyzed. The theoretical and methodological research tools, which helps reproduce adequate picture of Ukrainian literature of the late nineteenth century, is represented. The subject of peculiar attention is poet’s philosophical views, his psychological type in artistic works, the aesthetic concepts as the key to decoding the basic meaning of the poetic work of B. Hrinchenko and the tolerant appreciation of his pieces of work.